Factors influencing customers' purchase intention of counterfeit mobile phone : an empirical study in Malaysia - Bah, Aissatou Fatoumata (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
Counterfeiting activities have become a major global issue destroying the real industry. This study aims to identify several factors that affect consumers' decision to purchase counterfeit mobile phones in Malaysia by using the Theory of Planned Behavior (TPB). Apart from that, it will also investigate the influence of low price, past-experience, religious and ethical factors, attitude, subjective-norm, and Perceived behavioural control on the purchase intention of counterfeit mobile phone. Data was collected from 283 people living in the Klang Valley, Malaysia. For the data analysis, descriptive, reliability, exploratory factor analysis, correlation and regression analysis were conducted by using SPSS. Empirical findings of the study reveal that low price, subjective-norm and perceived behavioural control have a direct significant influence on the purchase intention of counterfeit mobile phone. However, the religious and ethical factors show an insignificant impact on the purchase intention of counterfeit mobile phone. These findings could assist policymakers and academicians to discover some strategies to combat this big phenomenon on the activities of purchasing counterfeit mobile phones in Malaysia.